Nationalism and economic development in modern Eurasia - Mosk, Carl. (New York : Routledge, 2013)
"This book advances a new theory of why nationalism emerged in the modern world. In particular it explains why nationalism and economic development are closely linked, and why warfare plays a crucial role in the spread of the nation-state system. It is based on qualitative and quantitative evidence over the period 1600 to 2000 for seven countries--Great Britain, France, Germany, Yugoslavia, the United States, Japan and China "--
pt. I. Nationalism, economic development, and warfare -- pt. II. Europe -- pt. III. Asia -- pt. IV. Implications and conclusions.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nationalism -- History; Nation-state -- History; Economic development -- History; Electronic books